2014
DOI: 10.1164/rccm.201404-0624oc
|View full text |Cite
|
Sign up to set email alerts
|

Integrative “Omic” Analysis of Experimental Bacteremia Identifies a Metabolic Signature That Distinguishes Human Sepsis from Systemic Inflammatory Response Syndromes

Abstract: Rationale: Sepsis is a leading cause of morbidity and mortality. Currently, early diagnosis and the progression of the disease are difficult to make. The integration of metabolomic and transcriptomic data in a primate model of sepsis may provide a novel molecular signature of clinical sepsis.Objectives: To develop a biomarker panel to characterize sepsis in primates and ascertain its relevance to early diagnosis and progression of human sepsis.Methods: Intravenous inoculation of Macaca fascicularis with Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 49 publications
2
99
0
Order By: Relevance
“…A similar systems biology analysis of sepsis was performed in a non-human primate (NHP) model and confirmed that carnitine esters were increased in septic animals [37]. RNAseq analysis was performed on the whole lungs taken from these animals.…”
Section: Metabolomic Changes In Sepsis Suggest An Energy Crisis In Nomentioning
confidence: 99%
See 3 more Smart Citations
“…A similar systems biology analysis of sepsis was performed in a non-human primate (NHP) model and confirmed that carnitine esters were increased in septic animals [37]. RNAseq analysis was performed on the whole lungs taken from these animals.…”
Section: Metabolomic Changes In Sepsis Suggest An Energy Crisis In Nomentioning
confidence: 99%
“…Recent advances in systems biology can minimize some weaknesses of the single omics methods by utilizing holistic approaches that compare multiple data streams for correlative molecular pathways in the host response. The integrative approach assumes that a comprehensive, hypothesis-agnostic description of the molecular changes can identify unbiased signatures that maybe lost in one-dimensional analyses [35, 37]. Moreover, the correlation of molecular networks and pathways in complementary datasets can potentially identify and prioritize likely causal molecular mechanisms.…”
Section: System Biology Analysis Of Clinical Samples Provides Unique mentioning
confidence: 99%
See 2 more Smart Citations
“…Several animal models have been used, testing different biofluids including blood [16][17][18][19][20], broncheoalveolar (BAL) fluid [16] and lymph [18] as well as tissue, such as lung [16,17], liver [17,21], kidney [22] and spleen [17,22]. Infections as diffuse as cerebral malaria [22], influenza [23], tuberculosis [17], peritonitis [16,18,24] and Escherichia coli sepsis [20] have been investigated.…”
Section: Metabonomics and Intensive Carementioning
confidence: 99%